ANALISIS BIBLIOMETRIK: TREND PENELITIAN ETNOMATEMATIKA DI JEMBER PADA MATERI GEOMETRI - Panglipur, Indah Rahayu (Universitas Insan Budi Utomo, 2024)
This research aims at bibliometric analysis so that data can be obtained that can be used as a reference regarding the diversity of ethnomathematics in geometric concepts that have been explored through research to be developed in mathematics learning. The novelty obtained from this research is that it is able to provide an overview and reveal the trend position of ethnomathematics research on geometry material in Jember. The benefit obtained can be used as a reference for learning process activities carried out at school. This research uses bibliometric visualization and bibliometric analysis to provide a structural overview of the field of qualitative research. Bibliometrics uses the Publish or Perish (PoP) and VOSviewer applications to obtain a research trend database. The research results show that the concept of geometry is found in several publications related to ethnomathematics in Jember. Applications of concepts related to this research are triangles, symmetry, parallel lines, straight lines, curved lines, and applied to batik motifs.